Шляхи реалізації корекційних завдань у роботі з дітьми з інтелектуальними порушеннями - Луканьова, Людмила Олексіївна (My University, 2025)
In the current context of social change, the idea of humanising education is becoming particularly important. This involves respecting the uniqueness of each individual and creating favourable conditions for their development in accordance with their individual abilities. One of the key areas of educational policy in Ukraine has become inclusive education — a form of education that ensures the integration of people with special educational needs into the general education system. People with intellectual disabilities constitute a special category of people who need specially organised conditions for learning, upbringing and socialisation. They should not be passive consumers of educational services, but active participants in the pedagogical process, subjects of their own development, adaptation and integration into society. The effective inclusion of such individuals in the education system is only possible with a holistic approach that takes into account their cognitive, behavioural and social characteristics. The relevance of introducing inclusive education for children with intellectual disabilities is explained by the fact that preschool and school age are the foundation for further personal development, so it is important to provide such children with access to quality education. This can be achieved by adapting educational programmes, creating an inclusive environment, systematically training specialist teachers, and with the support of parents. All this contributes to the realisation of the child's right to education. This article analyses and theoretically substantiates specific approaches to the implementation of inclusive education for children with intellectual disabilities, as well as identifying effective conditions for their maximum involvement in the educational process.

У сучасних умовах суспільних змін особливо важливою стає ідея гуманізації освіти, яка передбачає повагу до унікальності кожної людини та створення сприятливих умов для її розвитку, відповідно до індивідуальних можливостей. Одним із ключових напрямів освітньої політики в Україні стала інклюзивна освіта — форма навчання, яка забезпечує інтеграцію осіб з особливими освітніми потребами в загальноосвітній простір. Особи з інтелектуальними порушеннями становлять особливу категорію людей, які потребують створення спеціально організованих умов для навчання, виховання та соціалізації. Вони не повинні бути пасивними споживачами освітніх послуг, а виступати активними учасниками педагогічного процесу, суб'єктами власного розвитку, адаптації та інтеграції в суспільство. Ефективне включення таких осіб у освітню систему можливе лише за цілісного підходу, що враховує їхні когнітивні, поведінкові й соціальні особливості. Актуальність запровадження інклюзивного навчання дітей з інтелектуальними порушеннями пояснюється тим, що дошкільний та шкільний вік є фундаментом для подальшого розвитку особистості, тому важливо забезпечити таким дітям доступ до якісної освіти. Цього можна досягти шляхом адаптації освітніх програм, створення інклюзивного середовища, системної підготовки фахівців-педагогів, а також за підтримки з боку батьків. Усе це сприяє реалізації права дитини на освіту. У даній статті проведено аналіз і теоретичне обґрунтування специфічних підходів впровадження інклюзивної освіти для дітей з інтелектуальними порушеннями, а також визначення ефективних умов для їхнього максимального залучення в освітній процес.
Keywords: Inclusive education; children with intellectual disabilities; cognitive disorders; correction of early developmental disorders